ANALISIS UNSUR EKSTRINSIK NOVEL SELIMUT MIMPI KARYA R. ADRELAS SEBAGAI MEDIA PEMBELAJARAN SASTRA - Missi Missi; Ati Rosmiati (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to analyze the Extrinsic Elements of the Selimut Dream Novel by R. Adrelas. The data source of this research is the novel Selimut Dream by R. Adrelas totaling 352 pages published by the publisher Scritto Books Publisher, first issue, 2018. This type of research is descriptive qualitative. The technique used is the listening technique, and the note-taking technique is reading repeatedly, grouping data, describing, analyzing, drawing conclusions, compiling analysis results, and reflecting. Based on the results of this study, it can be concluded that there are extrinsic elements in the novel Selimut Dream by R. Adrelas, among others: Religious values ​​consist of: faith, prayer, prayer. Moral values ​​consist of: responsibility, honesty, patience, sincerity, respect. Cultural values ​​consist of: Cultural values ​​in Pasundan Banten and Jakarta. Social values ​​consist of: affection, caring, helping, sharing.